Debt-led-growth hypothesis (DLGH) and productive constraints: An empirical evaluation of African economies - Ikechukwu Kelikume; Adewumi Otonne (International Journal of Management, Economics and Social Sciences (IJMESS), 2022)
This study investigated the role of productive capacity by testing the debt-led growth hypothesis in 54 African Countries. This study is motivated by the rising nature of external debt following the fallout of the Covid-19 and the neglect of productive capacity in the debt-growth empirical relations, a variable found to be a necessary determinant based on theory. The study employed panel data from 2000 to 2018 and Pooled OLS, Fixed effect and Panel Generalized Method of Moment (GMM) as the panel estimators. Furthermore, two models were estimated for each panel estimator to capture the effect of the introduction of productive capacity on the debt-growth nexus - a model with and without the productive capacity index. The study results showed that the marginal contribution of external debt to growth is negative in the African countries, while productive capacity plays a significant role in the debt-growth nexus. Moreover, productive capacity moderates the relationship between debt and growth and reduces debt's negative impact on growth. The implication is that policymakers need to introduce policies to facilitate the growth-enhancing impact of debt and boost the countries' national income.
Keywords: E10; F35; O47; 330; Productive capacity; external debt; economic growth; debt-led-growth hypothesis; African countries